Peramalan Perbandingan Metode Exponential Moving Average dan Weighted Moving Average Dalam Peramalan Angka Kemiskinan Di Kabupaten Pamekasan: Perbandingan Metode Exponential Moving Average dan Weighted Moving Average Dalam Peramalan Angka Kemiskinan Di Kabupaten Pamekasan - Eka Yanti; Luluk Sarifah (Alpha-Epsilon: Journal of Mathematics, 2025)
This study aims to predict the best method in a forecasting system using the Exponential Moving Average (EMA) and Weighted Moving Average (WMA) methods. In the simulation stage, the data used is the poverty rate data in Pamekasan Regency from 2015 to 2024 as actual data to predict the 2025 data. Meanwhile, the comparison process is carried out by looking at the accuracy level of each method based on the MSE and MAPE values. Based on the results of data simulations from the two methods tested, it is known that the Exponential Moving Average (EMA) and Weighted Moving Average (WMA) are suitable for predicting poverty rates in Pamekasan Regency, because the resulting MAPE value is between 20% -50%.